Design and research of clearing-settlement platform based on blockchain technology - Shuting LI; Jinke LIU; Na CHEN (Dianxin kexue)
The business status of domestic roaming and clearing services of telecom operators and the problems and challenges faced after the arrival of 5G were analyzed.The blockchain technology represented by distributed ledgers and smart contracts were introduced,and the domestic clearing-settlement platform based on blockchain technology was formulated.The solution was elaborated from the logic architecture,business architecture,transaction flow and scalability of the clearing platform.Finally,based on the landing plan of the domestic clearing platform,combined with the business development needs under the new situation,the design ideas of partner settlement,inter-network settlement and international roaming settlement were provided.